1996
DOI: 10.2166/wst.1996.0440
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic loading tests for final settling tanks

Abstract: Dynamic experiments conducted in a pilot scale settling tank at Zurich's wastewater treatment plant (WWTP) are presented. The experiments were carried out with real activated sludge. They showed that vertical perforated walls transverse to the main flow direction are very beneficial particularly for wet-weather flow. The increase of the effluent suspended solids concentration is significantly dampened with dynamic hydraulic loading. Installing several perforated walls enables uniform velocity profiles to be at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“… Kim and Pipes (1996) in their assessment of the predictability of MLSS and sludge blanket depth at the Western Regional Treatment Plant in Chester, Pennsylvania during transient hydraulic conditions, noted that at peaking factors of 1.3 to 1.7 effluent suspended solid concentrations varied from 16 to 169 mg/L. Dynamic testing of final clarifiers at Zurich's Wastewater Treatment Plant revealed that doubling the overflow rate during a wet weather event can quadruple the effluent suspended solid concentration ( Baumer et al, 1996 ). While hydraulic overloading adversely affects clarifier performance by increasing overflow rate and creating turbulent nonquiescent settling, organic and suspended solid overloading increases MLSS, thus reducing the settling velocities dramatically in accordance with the Vesilind model.…”
Section: Discussionmentioning
confidence: 99%
“… Kim and Pipes (1996) in their assessment of the predictability of MLSS and sludge blanket depth at the Western Regional Treatment Plant in Chester, Pennsylvania during transient hydraulic conditions, noted that at peaking factors of 1.3 to 1.7 effluent suspended solid concentrations varied from 16 to 169 mg/L. Dynamic testing of final clarifiers at Zurich's Wastewater Treatment Plant revealed that doubling the overflow rate during a wet weather event can quadruple the effluent suspended solid concentration ( Baumer et al, 1996 ). While hydraulic overloading adversely affects clarifier performance by increasing overflow rate and creating turbulent nonquiescent settling, organic and suspended solid overloading increases MLSS, thus reducing the settling velocities dramatically in accordance with the Vesilind model.…”
Section: Discussionmentioning
confidence: 99%
“…However, the sludge was modeled by a non‐flocculent, clay suspension in their research and the effect of the porous wall on the flocculation enhancement cannot be verified. Baumer, Volkart, and Krebs () followed Krebs et al's () research and compared the effect of a solid and perforated baffle with different porosity on the performance of a pilot SST under dynamic loadings. The results showed that the perforated baffle performed better than the solid baffle under dynamic loading conditions, which can be helpful to maintain the stable performance of the SST during the wet weather.…”
Section: Applications Of Cfd Modeling Research and Engineering Practicementioning
confidence: 99%
“…Further improvements of existing secondary clarifiers can be achieved by the installation of vertical perforated walls according to Baumer et al (1996). By slowing down the bottom current, the total sludge mass stored in the final settling tank can be increased, which is especially useful in wet-weather conditions.…”
Section: Inlet Structurementioning
confidence: 99%